PENGARUH PELATIHAN DI PUSAT LAYANAN USAHA TERPADU KOPERASI USAHA MIKRO KECIL MENENGAH KABUPATEN CIANJUR - Sartika, Utami Dewi; Munjin, R. Akhmad; Salbiah, Euis (Jurnal Governansi, 2019)
Training is an effort to improve knowledges, skills and attitudes in improving performance, quality, and productivity. In this case, the government determined a mentoring program, namely Center for Integrated Services Small and Medium Micro Enterprises and Cooperatives in Cianjur Regency, in order to develop the small and medium micro enterprises and cooperatives. One of the Center for Integrated Services in guiding the development of the small and medium micro enterprises and cooperatives is training for the small and medium micro enterprises and cooperatives to improve the human resources. The purpose of this research is to describe the function of training in Center for Integrated Services Small and Medium Micro Enterprises and Cooperatives in Cianjur Regency. The theory of this research stems from Robinson’s theory, including at least four dimensions, namely training, skill, attitude, and benefit. This research uses descriptive method. Respondents of this research consist of 20 participants of training. The data is collected by using observation, interview, and questionnaire. The data collected by questionnaire is analyzed by using the Weight Mean Score formula to count the mean score. The result of this research indicate the mean score 4.08, included in the good criteria. Therefore, the implementation of training function in Center for Integrated Services Small and Medium Micro Enterprises and Cooperatives in Cianjur Regency influences the improvement of the training participant competence. Although there is the influence of the training on the attitude and quality necessarily improved in order to develop the small and medium micro enterprises and cooperatives in Cianjur Regency. Keywords: Training Function, Integrated Services, Small and Medium Micro Entreprises.